EVOLUTION AND PRACTICAL EFFECTIVENESS OF LAPAROSCOPIC NEPHRECTOMY TECHNIQUES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Laparoscopic nephrectomy has transformed modern urology by improving the management of both benign and malignant kidney diseases. This review outlines the evolution of laparoscopic techniques and evaluates their practical effectiveness in various clinical settings. Compared to open surgery, laparoscopic nephrectomy provides better perioperative outcomes such as less blood loss, shorter hospital stays, reduced pain, and improved cosmetic results, while maintaining comparable oncological safety. Advances like 3D visualization, energy devices, and robotic assistance have enhanced precision and broadened its use for complex cases. Current evidence supports laparoscopic nephrectomy as the preferred method for selected patients, with ongoing innovations continuing to expand its potential.